The Bunnies' Picnic - Lezlie Evans
Bunny one and bunny two get ready to make yummy stew! All the bunnies, one through eight, are preparing a great feast. But ... oh, no! Bunny one and bunny two didn't mean to spill the stew. What's this blue bunny crew to do? Luckily, the bunnies work together to save the day. Adorable illustrations and rhythmic text are sure to make counting cooperation fun for every young reader.